Guidelines for process safety metrics (Wiley ; Center for Chemical Process Safety, 2010)
The purpose of this book is to provide guidance to many levels of the organization when implementing or improving existing corporate process safety metrics. Although the process safety leaders in the company will have the strongest interest, it is equally important that others in leadership roles also read this book and work together with the process safety leaders in selecting and implementing the appropriate metric programs. This book provides guidelines and examples of effective practices for the development and use of process safety leading and lagging metrics; while also providing basic i.